The next generation of current measurement for ionization chambers. (September 2020) - Fitzgerald, R.; Bergeron, D.E.; Giblin, S.P.; Jarrett, D.G.; Judge, S.M.; Michotte, C.; Scherer, H.; Zimmerman, N.M.
Abstract: Re-entrant ionization chambers (ICs) are essential to radionuclide metrology and nuclear medicine for maintaining standards and measuring half-lives. The requirements of top-level metrology demand that systems must be precise and stable to 0.1 % over many years, and linear from 10 −14 A to 10 −8 A. Thus, laboratories depend on bespoke current measurement systems and often rely on sealed sources to generate reference currents. To maintain and improve present capabilities, metrologists need to overcome two looming challenges: ageing electronics and decreasing availability of sealed sources. Possible solutions using Ultrastable Low-Noise Current Amplifiers (ULCAs), resistive-feedback electrometers, and (quantum) single-electron pumps are reviewed. Broader discussions of IC design and methodology are discussed. ULCAs show promise and resistive-feedback systems which take advantage of standard resistor calibrations offer an alternative. Highlights: Reviews the importance of ionization chambers for radionuclide metrology. Establishes challenges to maintaining and improving ionization chamber systems. Evaluates the advantages and limitations of existing and new technology, including single electron pump (SEP). Identifies solutions using either ultrastable low-noise current amplifiers (ULCA) or standard resistors.